The 2006 Electoral Process and its Innovations in the Peruvian Democratic System - Gálvez, José Francisco (2006)
Suffrage did not originate as the right we know today, but was aligned with the social interests of those groups that held power. This paper offers an overview of the evolution of the electoral process in the Peruvian democratic system, with a focus on the latest contributions made in 2006. The author discusses the constitutional reform that granted police and military personnel the right to vote, the implementation of the electoral barrier, and the Political Parties Act. Additionally, the author evaluates the possibility of non-reelection for congressional positions and highlights pending tasks such as granting the right to vote for incarcerated individuals and eliminating the preferential vote.